Rootstock effects on leaf function and isotope composition in apple occurred on both scion grafted and ungrafted rootstocks under hydroponic conditions - Biasuz, Erica Casagrande; Kalcsits, Lee (Frontiers in Plant Science, 2023)
Rootstocks are used in modern apple production to increase productivity, abiotic and biotic stress tolerance, and fruit quality. While dwarfing for apple rootstocks has been well characterized, the physiological mechanisms controlling dwarfing have not. Previous research has reported rootstock effects on scion water relations. Root architecture and variability in soil moisture across rooting depths can also contribute to these differences among rootstocks in the field. To exclude these effects on rootstock behavior, scions were grafted onto four different rootstocks with varying effects on scion vigor (B.9, M.9, G.41 and G.890). Non-grafted rootstocks were also grown to examine whether the effects of rootstock occurred independently from scion grafting. Plants were grown in a greenhouse under near steady-state hydroponic conditions. Carbon (δ13C), oxygen (δ18O) and nitrogen (δ15N) isotope composition were evaluated and relationships with carbon assimilation, water relations, and shoot growth were tested. Rootstocks affected scion shoot growth, aligning with known levels of vigor for these four rootstocks, and were consistent between the two scion cultivars. Furthermore, changes in water relations influenced by rootstock genotype significantly affected leaf, stem, and root δ13C, δ18O, and δ15N. Lower δ13C and δ18O were inconsistently associated with rootstock genotypes with higher vigor in leaves, stems, and roots. G.41 had lower δ15N in roots, stems, and leaves in both grafted and ungrafted trees. The effects of rootstock on aboveground water relations were also similar for leaves of ungrafted rootstocks. This study provides further evidence that dwarfing for apple rootstocks is linked with physiological limitations to water delivery to the developing scion.